PENGARUH PRODUK TABUNGAN DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN MENABUNG PADA KJKS BMT BINNA UMMAT SEJAHTERA KEC. LASEM - Muhammad Dwi Ari Susanto; Handoyo Djoko Waluyo; Sari Listyorini (Jurnal Ilmu Administrasi Bisnis, 2012)
KJKS BMT BUS is one of principled Islamic financial institutions. One of the products offered by KJKS BMT BUS is a savings product. Any problems that occur in KJKS BMT BUS is the achievement of targets that can not be fulfilled. The factors thought to effect the saving decision is a savings product and service quality. If the attractive savings products and service quality the company is doing well, then the decision to save a high savings can be achieved. The purpose of this research was to determine whether there is influence between saving product and service quality of the saving decisions on KJKS BMT BUS district Lasem. The type of research is explanatory research. Sampling technique using the method of Simple Random Sampling that means the sampling a random member of the population without regard to strata in the population and members of the population is considered homogeneous. Therefore, the sample is totally contain 100 respondents. Data analysis technique used was simple linear regression analysis and multiple linear regression analysis with the tools SPSS 17 for Windows programs. The analysis of this research prove that as partially savings products had positive effect of saving decision with determination coefficient value is 22.1%, and service quality had positive effect of saving decision with determination coefficient value is 30.9%. And simultaneously savings products and quality service had positive effect of saving decision with determination coefficient value is 38.9%. The conclusion of this research is that the product savings and service quality affect of saving decision a partial, and simultaneously saving product and service quality affects to the saving decision. Advice that can be delivered is KJKS BMT BUS should improve the quality of products to attract savings in order to save. KJKS BMT BUS also needs and further improve the quality of service to customers, although the quality of service is good.